Alat Peraga Kebencanaan Untuk Literasi Mitigasi Bencana Gempa Bumi - Asri Ratna Sari (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to: (1) To determine the level of understanding of students about earthquakes and anticipatory steps, (2) To test the effectiveness of earthquake process simulation in order to increase mitigation literacy. This research method uses survey and simulation methods. The population in this study was taken by students of class VII D as a sample representing the population of SMP N 2 Banjarnegara. Class VII D has several students who live in disaster-prone areas. The results of this study indicate that the simulation uses disaster aids or Disaster Aid, increases the understanding of VII D students about earthquakes and anticipatory steps, and optimizes the level of understanding of students in class VII D about disaster mitigation literacy, and it is hoped that this research will be useful in providing an understanding of school residents. about the urgency of human behavior to save themselves when there is a disaster.